DETECTION OF SOIL WATER CONTENT IN TEA (Camellia sinensis) PLANTATION THROUGH SPATIAL ANALYSIS USING AGRIRADAR TECHNOLOGY IN BOGOR, WEST JAVA - Elia Laila Rizqiyah; Restu Wulansari (Gunung Djati Conference Series, 2026)
Soil water content is a critical parameter for plants that influence nutrient absorption, plant growth, and plant metabolism. In tea (Camellia sinensis), soil water content must be monitored regularly. This study aims to develop a rapid and spatially approach to detect soil water content using Agriradar technology. The agriradar technology integrates radar sensing and multispectral imaging in the aerial vehicle (UAV) to generate spatial data across plantation areas. This device is able to detect soil water content so that spatial-based data is obtained from the area passed by the drone. Experiments were carried out by taking a case studies on tea plantations. This research was conducted from January-May 2025 in tea plantations located in Bogor, West Java, Indonesia. The results of this study indicate that soil water levels ranged from 22% to 25%, which is below the optimal limit of 30% required for optimal tea growth. Furthermore, soil water content below 10% are associated with inhibited shoot development and increased risk of plant mortality. The integration of Agriradar technology into precision agriculture practices can support cultivation management and improve fresh yield of the tea plantation.